PENGAWASAN PERILAKU HAKIM MAHKAMAH KONSTITUSI OLEH DEWAN ETIK - Mardiya, Nuzul Qur'aini (Jurnal Hukum dan Peradilan, 2017)
The Constitutional Court has a code of ethics and behavior of judges the constitution as the legal basis to carry out profession ethics. Due to his duty, judge of the constitution had potentially breaking the code of conduct and behavior of judges. In order to oversee the conduct of judges the constitution formed The Board of Ethics Judge Constitution (DE-HK) who has authority to check and give decision regarding of the reports on complaints and information through the media/the community related to alleged violations the code of conduct and behavior of judges the constitution as well as a violation of law constitutional court. The Board would have the authority to impose sanctions verbally and if the offense heavy, the board recommended the formation of an assembly of honor of constitutional court and make propose of the suspension of the judge the constitution, and if not proven The Board rehabilitates judge that concerned. This study is done in a juridical manner normative by looking at an object or target of regulation research, legislation and materials law other related supervision the conduct of judges the constitution by the board. Hence, within the revision on constitutional court law in National Legislation Program, it's important to do institutional strengthening the board of conduct and to ripen position the tribunal honor judges to carries out surveillance and checks for violation code of ethics and behavior by the judges.Keywords: code of ethics and behavior, The Board Of Ethics Judge Constitution, judge, supervision